Comparative Assessment of Synthetic and Natural Antioxidants: Synergistic Interactions Between Ebselen and Stigma maydis Extracts - Bahakim, Nasraddin Othman (Asian Journal of Pharmaceutics (AJP), 2025)
To explore the hydro-ethanolic Stigma maydis extract antioxidant activity alone and in combination with Ebselen, a water-soluble vitamin E antioxidant, through several in vitro parameters. Material and Methods: After authentication, the extract was prepared by boiling and filtering 20g of corn silk. Various concentrations (20–100 μg) were tested using DPPH, ABTS, catalase, hydroxyl, and nitric oxide scavenging assays. Antioxidant activity was measured by absorbance changes at specific wavelengths, and results were expressed as scavenging percentages. Data were analyzed using mean and standard deviation. Results and Discussion: The strong antioxidant property was observed as 44%, 62%, 67%,75% and 88% of scavenging activity inhibition against DPPH, 36%, 54%, 71%, 76% and 84% of ABTS scavenging activity, 35%, 54%, 71%, 79% and 85% against catalase, 30%, 46%, 61%, 69% and 80% of hydroxyl radical scavenging activity and 25%, 45%, 61%, 73% and 82% of nitric oxide scavenging activity was noted when the hydro-ethanolic S. maydis extract combined with Ebselen. Conclusion: Hydro-ethanolic S. maydis extract combined with Ebselen showed strong antioxidant properties that may be used to treat various life-threatening diseases.